Cognitive Creation Monopoly Game-Based Learning Media to Develop Children's Critical Thinking Skills in Group B: Indonesia - Ketut Vani Dwijayanti; Putu Aditya Antara; Dewa Gede Firstia Wirabrata (Thinking Skills and Creativity Journal, 2025)
The limited development of critical thinking skills in early childhood and the suboptimal use of instructional media constitute major challenges in creating meaningful and contextual learning processes. This condition restricts children’s active engagement in learning activities that stimulate higher-order thinking skills. This study aims to develop a learning medium based on the Monopoli Kreasi Kognitif game, analyze the validity of its content and design, explore its practicality based on teachers’ and students’ responses, and examine its effectiveness in improving children’s critical thinking skills. This study employed a research and development approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects comprised 25 children from Group B. Data were collected through observation, interviews, and questionnaires, using instruments in the form of expert validation sheets, practicality questionnaires, and critical thinking tests. Data analysis was conducted using descriptive quantitative analysis and statistical testing. The results indicate that the Monopoli Kreasi Kognitif media was validated with an average feasibility index of 3.70 and demonstrated high practicality, as reflected in a 100% positive response from teachers and an 81.6% positive response from students. The effectiveness test using a paired-sample t-test revealed a value of t = 7.985 with Sig. (2-tailed) = 0.000 < 0.05, indicating a significant difference between pre-test and post-test results. The findings confirm that this game-based learning medium is effective in enhancing early childhood critical thinking skills and has important implications for the development of adaptable, concrete instructional media in early childhood education.